ILLOCUTIONARY ACTS IN “MIDNIGHT IN PARIS” MOVIE - Nuri Emmiyati; Indriani Indriani (Elite : English and Literature Journal, 2015)
Abstract This article aims to describe the types of illocutionary acts of main character in “Midnight in Paris” movie. It also aims to describe the type of illocutionary acts which is mostly used by the main character. It is a content analysis where the source of data is the “Midnight in Paris” movie directed by Woody Allen in 2011 which consisted of 245 utterances. The data are in the form of   main character’s 44 utterances and categorized into types of illocutionary acts based on Searle’s theory. Based on data analysis, the finding shows five types of illocutionary acts in main character’s utterances, namely assertive, directive, commissive, declarative and expressive. Assertive is mostly used by the main character. Key words: illocutionary acts, utterances, pragmatics, Midnight in Paris movie Abstrak Artikel ini bertujuan untuk memberikan gambaran tentang jenis-jenis tindak ilokusi dari tokoh utama dalam film “Midnight in Paris” yang disutradarai oleh Woody Allen pada tahun 2011. Artikel ini juga menggambarkan jenis tindak ilokusi yang palingt banyak digunakan oleh tokoh utama. Dengan menggunakan analisis isi,data yang berupa 44 ujaran yang diungkapkan oleh tokoh utama dikategorikan ke dalam jenis-jenis tindak ilokusi berdasarkan teori yang dikemukakan oleh Searle. Hasil analisis data menunjukkan bahwa terdapat lima jenis tindak ilokusi dari tokoh utama film tersebut, yaitu assertive, directive, commissive, declarative dan expressive. Assertive merupakan tindak ilokusi yang paling banyak digunakan oleh tokoh utama.  Kata kunci: tindak ilokusi, ujaran, pragmatic, film Midnight in Paris